Influência do tipo de uso e ocupação do solo no assoreamento do reservatório Bom Jardim, Uberlândia - MG - Martins, Caroline Soler (2018)
The objective of this work is the simulation of the quantity of sediments tributaries to a source of public supply. For that, a software called Soil and Water Asscessment Tool (SWAT) was used, which allows, through numerical simulations, to define the sediment production in a given reservoir. The same was applied to the Bom Jardim Reservoir in the city of Uberlândia (MG). Starting off on the hypothesis that there is a great relation between the type of use and occupation of the soil with the silting in water bodies: the more exposed the soil is, the greater the erosion and, consequently, the production of sediments in the reservoirs. In the modeling, soil type, slope of land and the type of land use and occupation present throughout the sub-basin area of Ribeirão Bom Jardim, using different scenarios of land use and occupation, varying the percentage of Agriculture replaced by Forest or the percentage of Pasture replaced by Forest, in order to verify the effect of this change in the production of sediments. By means of the overlapping of these data and the insertion of data of climatic stations, numerical results were generated on the sediment production of the real scenario and of the imposed scenarios in the studied area. It was observed that with the increase of Forest, substituted/replaced by Agriculture, the production of sediments was reduced. When replacing grassland by forest, a reduction in sediment was also observed, this reduction is increased with the increase of forest percentage. The substitution of Agriculture for Forest generated better results than the replacement of Pasture by Forest, since the area of the sub-basin of Ribeirão Bom Jardim accounts for 64,3% of its area covered by Agriculture and only 10,1% of Pasture. From the results of sediment production, the silting of the Reservoir was simulated by means of a program that makes this calculation from flow, sediment production, granulometry and reservoir volumes. Thus, it was possible to compare silting in the reservoir with conventional practices of land use currently existing in the study area, with silting generated in case more sustainable and conservationist practices were applied to the properties present in the sub-basin under study. The smaller the replacement of Agriculture or Grassland by Forest, the greater the silting of the reservoir, that is, the replacement of these areas by Forest generates a longer life span for the reservoir.